Tooth brushing techniques among students attending King Solomon College, Gboko, Benue State, Nigeria - Iba, Bemhemba; ADAMU, VE (Orapuh Journal, 2021)
IntroductionOral diseases constitute a major public health problem and poor oral hygiene practices contribute to the global burden of oral diseases. The most effective way to prevent oral diseases like dental caries, gingivitis, and periodontitis is the removal of dental plaque from oral tissues. Self oral hygiene maintenance is by tooth brushing, mouth rinsing, and dental flossingPurpose The purpose of this study was to assess the techniques used for tooth brushing among students attending King Solomon College, Gboko, Benue State, Nigeria with a view to enrich oral health education messages in the context. Materials and methodsA sample of 135 students was selected from the school population, using the simple random sampling technique. Data was obtained using personal interviews and observation. Data obtained were analyzed using the Statistical Package for Social Sciences (SPSS) version 20 (IBM Corporation). Chi-square test was used to determine the statistical significance of observed differences in the cross-tabulated variables. The significance level was set at 5% (p<0.05).Results The results of the study showed that none of the participants (0.0%) adopted the correct technique of tooth brushing (the roll technique). The majority of the participants (92.6%) used the horizontal technique while 4.4% and 3.0% represented the vertical and random techniques, respectively. Age (p=0.969) and gender (p=0.128) were not significantly related to tooth brushing techniques (p>0.05). Conclusion There is the need to organize oral hygiene awareness programmes to help educate people on the need to adopt the roll technique of tooth brushing to promote effective dental plaque removal and, by extension, the prevention of oral diseases.